STRATEGY TO CUT DOWN THE IMPORTED CONTAINER’S DWELLING TIME IN SEMARANG CONTAINER TERMINAL (TPKS) - Anis Rohayani; Jozef Bambang Tri Joga; M Nahar (JOBS (Jurnal Of Business Studies), 2015)
The study is about the strategies to cut down the imported container’s dwelling time in TPKS.Imported Container's dwelling time is the total time starting from the container is discharged offthe vessel up to the container reach the getting – out terminal. The impact of high dwelling timeis the increasing of YOR (Yard Occupancy Ratio) and the decreasing of BOR (Berth OccupancyRatio). The utilization of the Container Yard will increase, then the utilization of the dock relatedto loading and unloading containers will decrease for the next vessel. If the CY is fully stackedwith containers, certainly, there will be no more space for newly-coming containers, then thecongestion will happen. Importers who have the newly-coming containers will get loss, becausethey have to pay more for demurrage cost. Besides, they have to stop their production processesbecause the goods are still in the Port. The purposes of the study are explain how to complete the clearance processes, to know the internal and external factors of TPKS, to find the strategies with SWOT analysis to decrease theimported container’s dwelling time in TPKS.The method of collecting data used survey, observation, documentation, literature study and thequestionnaire. The analysis technique used SWOT analysis to know the TPKS condition and tofind the appropriate strategies.The results shows that the position TPKS in Quadrant I with coordinate 0.69:0.57, meaning thatthe suitable strategy used is supporting the aggressive growth policy (Growth OrientedStrategy). After compile the SWOT Matrix, then the strategies were found: enhance theperformance in each work, maintenance and rejuvenation equipment, provide new ground forinterchange and parking area, availability counter officer in business for 24 hour, theeffectiveness of each duty, optimization of the existing parking area, optimizing the operation ofexisting CC, optimization the counter during working hours. Keywords: Imported container’s dwelling time, SWOT